2011
DOI: 10.1007/s10557-011-6339-z
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren and Valsartan Reduce Myocardial AT1 Receptor Expression and Limit Myocardial Infarct Size in Diabetic Mice

Abstract: AL, dose dependently limited myocardial IS in mice with type-2 diabetes mellitus. At doses shown to limit IS in non-diabetic animals, VA failed to reduce IS in Db/Db mice. However, at higher dose (16 mg/kg/d), VA reduced IS. Both drugs reduced the expression of AT1R and increased myocardial levels of the longevity genes Sirt1 and PGC-1α along with increased Akt and eNOS phosphorylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 78 publications
(109 reference statements)
4
12
0
Order By: Relevance
“…Animal studies also showed that treatment with losartan induced the tubular expression of SIRT1. In support of our results, it has been reported that treatment with other ARBs, such as telmisartan and valsartan, increased the expression of SIRT1 in skeletal muscle cells of obese db/db mice and in myocardial cells of type-2 diabetes mellitus mice, respectively [27,28]. In addition, we also found that the inhibitory effect of losartan on the ER stress was mediated through the up-regulation of SIRT1.…”
Section: Discussionsupporting
confidence: 91%
“…Animal studies also showed that treatment with losartan induced the tubular expression of SIRT1. In support of our results, it has been reported that treatment with other ARBs, such as telmisartan and valsartan, increased the expression of SIRT1 in skeletal muscle cells of obese db/db mice and in myocardial cells of type-2 diabetes mellitus mice, respectively [27,28]. In addition, we also found that the inhibitory effect of losartan on the ER stress was mediated through the up-regulation of SIRT1.…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, by applying oral doses that were over 10 times higher than those used in humans (62.5 mg/kg p.o. per day versus 150-300 mg/day in humans), we were able, as in previous studies [21,22], to achieve a degree of RAS blockade that yielded the same BP-lowering effects as losartan at 60 mg/ kg p.o. per day.…”
Section: Discussionsupporting
confidence: 75%
“…per day; a kind gift of Novartis Pharmaceuticals, Basel, Switzerland), or propranolol (50 mg/kg p.o. per day; Sigma, St. Louis, Missouri, USA) in drinking water, as described before [13,15,21,22].…”
Section: Treatmentmentioning
confidence: 99%
“…Subcutaneous 0.1 mg/kg buprenorphine was administered, the chest was closed, and mice were allowed to recover from anesthesia. Twenty-four hours after reperfusion, mice were reanesthetized, the coronary artery was reoccluded, Evan's blue dye (3%) was injected into the right ventricle, and mice were euthanized under deep anesthesia (70).…”
Section: Ismentioning
confidence: 99%
“…Areas of the AAR and IS in each slice were determined by planimetry, converted into percentages of the whole for each slice, and multiplied by the weight of the slice. The results were summed to obtain the weight of the myocardial AAR and IS (70).…”
Section: Determination Of the Aar And Ismentioning
confidence: 99%